Preliminary Report of the Safety and Tolerability of 1 Hz Repetitive Transcranial Magnetic Stimulation in Temporal Lobe Epilepsy. (6th May 2022) - Gersner, Roman; Oberman, Lindsay M.; Sanchez, Maria J; Chiriboga, Nicolas; Kaye, Harper L; Pascual-Leone, Alvaro; Zangen, Abraham; Rotenberg, Alexander
Background: Low frequency (≤1 Hz) repetitive transcranial magnetic stimulation (rTMS) has been shown to suppress cortical excitability and is beginning to be trialed for the treatment of refractory epilepsy. Purpose: As a step toward a larger trial, the current pilot study was aimed to test the tolerability and safety of temporal lobe rTMS using H-coil for the treatment of temporal lobe epilepsy (TLE). Research Design: 1800 pulses of active or sham rTMS were applied 5  days a week for 2 weeks over the temporal lobe of the affected hemisphere. Results: Nine participants were enrolled and randomized to verum or sham stimulation. One participant dropped out from the sham group after 5 rTMS sessions. In-session, 3 patients had typical seizures during sham stimulation. One patient had seizures also during active stimulation (albeit fewer than during sham). Minor reported adverse events during stimulation otherwise included transient neck pain and headache, and were reported in equal numbers in both groups. Major adverse events were not reported. Our results indicate that H-coil rTMS was well-tolerated. Conclusion: Given the relatively high prevalence of individuals with TLE who are treatment-resistant and the preliminary results of this study, we suggest that a larger safety and efficacy trial of 1 Hz rTMS for the treatment of TLE is warranted.